Competency Development of Quality Control in Automotive Companies to Improve Service Quality - Nanda Tejaningrum Vera; Suryanto Suryanto (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The QC team provides innovation improvement ideas conducted by other departments until the output is produced perfectly using the concept of Plan-Do-Check-Action (PDCA), while the QC function in the context of sales and after-sales here is to control the service process of each dealer to comply with company standards. QC team must have a qualified knowledge and ability which described the ability including providing services, responsive, trustworthy and have empathy in running relationships in the team and consumers. One of the techniques that can be used today for Quality Control Sales and After Sales is the technology called Customer Relationship Management system (CRMs) which will facilitate qc work in terms of fulfilling the components of PDCA. Therefore, each QC team must have the appropriate level of education qualifications, technological operating skills and analytical power to be able to affect the productivity of the company.